2013
DOI: 10.1097/nmc.0b013e31826aa855
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Synthesis of Women's Experiences of Cesarean Birth

Abstract: It is important for healthcare professionals to realize women experience similar physical and emotional difficulties irrespective of whether the cesarean was emergent or planned. The overarching themes of (a) in your hands and (b) scared to death reveal the importance of assessing the woman's level of knowledge about cesarean birth throughout the pregnancy so misconceptions can be rectified and correct information can be provided. Healthcare professionals need to be aware of the differences in perspectives abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 13 publications
(50 reference statements)
4
17
1
Order By: Relevance
“…Future studies could compare the women's perceived reasons for the cesarean with the actual diagnosis listed by the health-care provider. Regardless of reasons for the cesarean or the information women used, the results of this study indicate the participants were satisfied with their decision and the information provided, which is contrary to other findings (Kolip & Buchter, 2009;Puia, 2013). Although the results indicated the women were satisfied with the information provided, the actual content of the discussions or the context of the conversations were not recorded; therefore, it is not clear how the interactions may have affected the women's decisions and recollections.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Future studies could compare the women's perceived reasons for the cesarean with the actual diagnosis listed by the health-care provider. Regardless of reasons for the cesarean or the information women used, the results of this study indicate the participants were satisfied with their decision and the information provided, which is contrary to other findings (Kolip & Buchter, 2009;Puia, 2013). Although the results indicated the women were satisfied with the information provided, the actual content of the discussions or the context of the conversations were not recorded; therefore, it is not clear how the interactions may have affected the women's decisions and recollections.…”
Section: Discussioncontrasting
confidence: 55%
“…The women's desire for more information was expressed in a metasynthesis conducted on 10 qualitative studies with a combined sample of 3,721 women (Puia, 2013). Six overarching themes emerged: scared to death, in your hands, out of control, broken body and soul, empty heart and arms, and shattered dreams.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A metasynthesis of the experiences of women from Australia, the USA, Finland, the UK, Canada and Japan, who underwent caesarean section, showed that they associated lack of information and knowledge with loss of control and powerlessness during the process of childbirth 23. Another review of studies from the USA, the UK and Canada showed that lack of information on the full range of health services available was a major challenge for marginalised women to accessing healthcare 24.…”
Section: Resultsmentioning
confidence: 99%
“…The WHO's framework of organisational management strategies to improve QoC does not emphasise interpersonal communication as a specific strategy for improving QoC. However, issues related to ‘communication’ were highlighted in several studies 23 24 35 36. Furthermore, a systematic review of interventions to improve communication between health professionals and pregnant women during maternity care suggested that improved interpersonal communication could increase acceptability and satisfaction,30 but its AMSTAR score was <3 and thus ranked low in methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation